Carcinoma buccal mucosa with cutaneous metastasis: An unusual presentation - Singhal, Lalita; Kumar Gupta, Rishi; Bhatnagar, Mohit; Paul, Briju; Agrawal, Diksha (Indian Journal of Case Reports, 2024)
Head-and-neck cancer is a common cancer in India. Oral cavity cancer accounts for 50% of all head and neck sites. The most common sites of distant metastasis are the lung, liver, and bone. The incidence of cutaneous metastasis is a very rare site. We report a case of early-stage carcinoma buccal mucosa post-surgery and adjuvant radiotherapy developed skin metastasis shortly after completion of treatment. A 37-year-old female non-smoker, non-alcoholic diagnosed with early-stage carcinoma right buccal mucosa cT1N0M0. She underwent surgery of wide local excision with marginal mandibulectomy and extended supra-omohyoid neck dissection. In post-surgery, the histopathological report was moderately differentiated squamous cell carcinoma, pT2N1Mx. She completed her adjuvant radiotherapy 59.4Gy/33 fractions with six cycles of concurrent chemotherapy cisplatin 40 mg/m2. She developed difficulty in swallowing, increased oral secretions, and thickening over right-sided scar marks shortly after 10 weeks of completion of treatment. Rapidly, she developed multiple cutaneous nodules over both sides of the entire face and neck. Dermal biopsy reveals metastatic squamous cell carcinoma. Skin metastasis from head-and-neck malignancy is an uncommon entity and in the early stage, it is very rare. Initially, it is difficult to diagnose as it looks like some disseminated bacterial or fungal infection but we should always keep in mind this entity as cancer can metastasize and present in any atypical forms.